Improvement of dual-fuel biodiesel-producer gas engine performance acting on biodiesel injection parameters and strategy. (1st December 2017) - Carlucci, A.P.; Ficarella, A.; Laforgia, D.; Strafella, L.
Abstract: Dual-fuel biodiesel-producer gas combustion has shown potential in reducing nitric oxides and particulate emission levels compared to only diesel operation; however, engine overall efficiency is slightly penalized, while the main drawbacks are represented by the higher levels of total hydrocarbons and carbon monoxide emissions. In this work, the improvements in the combustion development deriving from the splitting of the liquid fuel injection at low loads have been assessed using a 0.51 L single-cylinder research diesel engine equipped with a high pressure common rail injection system and operated in dual-fuel mode. In this case, a synthetic producer gas was used as inducted gaseous fuel, while biodiesel was used as pilot fuel. Initially, the spray morphology was characterized in a constant-volume vessel for different values of injection duration and pressure, as well as vessel backpressure. Then, the experimental campaign, run on the engine at 1500 rpm, was divided in two sessions. During the former, only one pilot injection of constant fuel amount (11 mm 3 /cycle) was performed, the rail pressure was set equal to 500 or 1000 bar, the injection timing was varied in the range −50 ÷ 5 degrees crank angle after top dead center while the amount of gaseous fuel inducted in the cylinder was varied on three levels. During the latter, the pilot fuel amount, kept equal to the one pilot injection tests, was split in two smaller injections and the effect of the dwell between them – varied in the range 5 ÷ 50 degrees crank angle – was investigated as well. The results of the first set of experiments revealed that pilot injection timing and pressure both affect the combustion development. This resulted in sensible variations on thermal and combustion efficiencies, and therefore on fuel conversion efficiency, the last one exhibiting higher values with pilot injection timing slightly advanced respect to top dead center and lower injection pressure. In these conditions, total hydrocarbons and carbon monoxide are lowered, while nitric oxides are increased. The amount of gas demonstrated to have a secondary effect on combustion development and emissions levels at the exhaust. Splitting pilot injection, demonstrated to be an effective way to increase fuel conversion efficiency and to reduce the levels of all the pollutant species compared to the single pilot injection strategy. Based on the extensive experimental activity described in this paper, a dwell ranging between 10 and 30 degrees of crank angle, combined with a first injection timing ranging between 35 and 20 degrees of crank angle before top dead center guarantee the highest fuel conversion efficiency and the lowest pollutants emission levels. Injection pressure confirmed to be a significant factor in affecting the combustion development, while a secondary effect was determined by the gaseous mass inducted in the cylinder. Ultimately, pilot injection splitting demonstrated to be an effective way for improving gaseous fuel combustion in dual-fuel mode at low load (lean mixture) conditions.